Some determinants and consequences of attachment styles at work - Uzunkoca, Ülfet (My University, 2022)
The objective of this paper was to highlight the attachment styles are significant construct at organizational settings. Correspondingly, the study aimed to estimate attachment styles at work in terms of individual factors (generalized attachment style) and work environment factors (psychological safety, interactional justice, managerial affect-based trust, supervisor support), and its relationship with emotional exhaustion and exploratory behaviours. The sample consisted of 556 employees working in various sectors and different organizations in Turkey. Hypothesized relationships related to determinants of the attachment styles at work were tested with stepwise regression analysis (forward inclusion). Moreover, hypothesized relationships related to consequences of attachments styles at work were tested with t-test and one-way ANOVA. Predictably, the results revealed that attachments styles at work is a significant construct in understanding work-related attitudes and behaviours namely, emotional exhaustion and exploratory behaviours. As to determinants of attachment styles at work the results showed that individual factors, namely one’s generalized attachment styles was the major determinants of one’s attachment styles at work. Moreover, the results showed that team level perceived work environment such as psychological unsafety is a better predictor than both individual level perceived work environment and positive work environment such as psychological safety. Detailly, psychological unsafety influenced both secure and fearful as well as with preoccupied attachment at work. Moreover, it also influenced dismissing attachment styles at work who had less than 2 years’ experience in the same group. Whereas psychological safety only influenced fearful attachment styles at work. In terms of individual level perceived work environment, the results revealed that perceived interactional justice had power to recreate secure attachment styles at work, and the dismissing attachment styles at work who had model of office working. However, individual level perceived environment namely, supervisor support and managerial trust showed no influence on recreating attachment styles at work.

Bu tezin amacı bağlanma stillerinin örgütsel ortamlarda önemli bir yapı olduğunu vurgulamaktır. Bu doğrultuda çalışmada, bireysel (genel bağlanma stili) ve çalışma ortamı (psikolojik güvenlik, etkileşimsel adalet, yönetici güveni, yönetici desteği) faktörleri temelinde işte bağlanma stillerinin belirleyicilerini tespit etme ve duygusal tükenme ile keşfedici davranışlar ile ilişkisinin ortaya konması amaçlanmıştır. Örneklemi Türkiye'de çeşitli sektörlerde ve farklı kuruluşlarda çalışan 556 çalışan oluşturmuştur. İşte bağlanma stillerinin belirleyicileri ile ilgili hipotezler regresyon analizi ile test edilmiştir. İşte bağlanma stillerinin iş çıktılarıyla ilgili hipotezler ise t-testi ve tek yönlü ANOVA ile test edilmiştir. Beklenildiği gibi sonuçlar işte bağlanma stillerinin işle ilgili tutum ve davranışları, yani duygusal tükenme ve keşfedici davranışları anlamada önemli bir yapı olduğunu ortaya koymuştur. İşte bağlanma stillerinin belirleyicilerine ilişkin sonuçlar, bireysel faktörlerin, yani kişinin genel bağlanma stilinin, kişinin işte bağlanma stilinin ana belirleyicisi olduğunu göstermiştir. Bununla birlikte, sonuçlar psikolojik güvensizlik gibi ekip düzeyinde algılanan çalışma ortamının hem bireysel düzeyde algılanan çalışma ortamından hem de psikolojik güvenlik gibi olumlu çalışma ortamından daha iyi bir yordayıcı olduğunu göstermiştir. Ayrıntılı olarak, psikolojik güvensizlik hem işte güvenli hem de işte korkulu bağlanma stiliyle birlikte işte saplantılı bağlanma stilini de etkilediğini göstermiştir. Ayrıca, aynı grupta 2 yıldan az deneyim olması durumunda işte kayıtsız bağlanma stilini de etkilemiştir. Diğer yandan psikolojik güvenlik sadece işte korkulu bağlanma stilini etkilemiştir. Bireysel düzeyde algılanan çalışma ortamı açısından sonuçlar ise, algılanan etkileşimsel adaletin işte güvenli bağlanma stilini ve ofis çalışması modelinde işte kayıtsız bağlanma stilini yeniden şekillendirme gücüne sahip olduğunu ortaya koymuştur. Bununla birlikte, bireysel düzeyde algılanan çevre, yani yönetici desteği ve yönetici güveni, işte bağlanma stillerinin yeniden şekillendirmesinde bir etkisi olmadığını göstermiştir.
Keywords: attachment styles; Business; duygusal tükenme; emotional exhaustion; exploratory behaviours; İşletme; keşfedici davranışlar; organizational behaviour bağlanma stilleri; örgütsel davranış; psikolojik güvenlik; psychological safety